2022
DOI: 10.1002/slct.202104333
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 2‐Amino‐4H‐1, 3, 4‐thiadiazine‐5(6H)‐one Derivatives and Their In Vitro Antitumor Investigation

Abstract: Novel 2‐Amino‐4H‐1,3,4‐thiadiazine‐5‐(6H)‐one derivatives 3–6 were designed, synthesized, and assessed for their anticancer effects on MCF‐7 and A549 cell lines. The cytotoxicity screening found several active compounds. Meanwhile, compound 5 b exhibited the strongest cytotoxic activity compared to Doxorubicin (DOX). Furthermore, DNA flow cytometry investigation over MCF‐7 cells indicated that compound 5 b demonstrated arrest at G1/S stages of the cell cycle and induction of apoptosis by rising pre‐G1 stage. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In continuation with our research studies focusing on the synthesis and in vitro investigation of bioactive compounds with anticancer activity, we had concluded that 1,3,4‐thiadiazine derivatives are a potential hypothesis in the field of medicinal chemistry and drug industry (Mohammed et al., 2022). Several of the synthesized components were also noted to be efficient when investigated in vitro versus breast (MCF‐7) and lung (A549) cancer cell lines for their ability to inhibit cell proliferation.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…In continuation with our research studies focusing on the synthesis and in vitro investigation of bioactive compounds with anticancer activity, we had concluded that 1,3,4‐thiadiazine derivatives are a potential hypothesis in the field of medicinal chemistry and drug industry (Mohammed et al., 2022). Several of the synthesized components were also noted to be efficient when investigated in vitro versus breast (MCF‐7) and lung (A549) cancer cell lines for their ability to inhibit cell proliferation.…”
Section: Introductionmentioning
confidence: 82%
“…All experimental groups' livers and kidneys served as the source of the specimens for the histopathological analysis, which were then sectioned, embedded in paraffin, preserved in 10% neutral buffered formalin, tainted with hematoxylin and eosin stain (H&E), and examined under a microscope condition (Mohamed et al., 2021; Mohamed, Ezzat, et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular modeling studies provide a valuable view of ligand–receptor binding and propose the mode of action of bioactive compounds. The biological activities of chemical compounds are attributed to the binding with key amino acids of the active site of cellular target proteins [ 35 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. To elucidate the mechanism by which the synthesized compounds conjugate with VEGFR2 activity, a molecular docking tool was used to examine the interactions of the compounds 3c and 4 toward VEGFR2.…”
Section: Methodsmentioning
confidence: 99%
“…Draw tool was used to construct the structure of the target compounds 3c and 4 . Then, the protonated 3D structure of target ligands 3c and 4 , the preparation of VEGFR2, and the docking studies were performed using MOE software as previously reported [ 35 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. The validity of the applied protocol was evaluated by performing a molecular docking of the original inhibitor to affirm the main interactions that exist in the reported crystal structure.…”
Section: Methodsmentioning
confidence: 99%